Investigating the problem of profit margin decrease in manufacturing companies through SD simulation. (30th June 2021) - Rabieh, Masood; Shahzadi, Fatemeh; Heydarbakian, Sadeq
Manufacturing companies struggle with many constraints affecting their profitability. Profitability, as a financial performance indicator, is thus a concern for managers, policymakers, and stakeholders of all manufacturing companies. This study aims to address the problem of profit margin decrease in such companies. To that end, system dynamics (SD) simulation was used to address the problem in a comprehensive manner. Real-world data was obtained from a dairy company in Iran, and after going through the SD modelling steps, the validity of the model was proved based on the reproduction of the historical data. The results reveal that under low customer income and high raw material prices, the net profit margin decreases to -0.002 and -0.001, at its minimum, and had 14% and 1.2% average reduction yearly for years between 2018 and 2028. The results also reveal that the behaviour of the net profit margin could be improved by two proposed policies.